Microbiological evaluation of artisanal mayonnaise supplied in snack bars in the city of Itapetinga – BA - Ponciano , Carolina da Silva; Lins, Raphael Patury; Oliveira , Geisa Sales; Silva , Jaqueline de Jesus; Domingues , Robson de Queiros; Barbosa, Monique Costa; Araújo , Antônia Cardoso Mendes de; Menezes , Lígia Miranda (Seven Editora, 2023)
Artisanal mayonnaise has gained popularity among consumers looking to enhance the flavor of food products. However, the production environment of these mayonnaise can become the main factor of contamination when there is no proper control of good manufacturing practices.  Therefore, the objective of this study was to evaluate the microbiota present in artisanal mayonnaise marketed in different locations in the city of Itapetinga-BA, as well as to compare it with the limits acceptable by the legislation for microorganisms such as Salmonella, total and fecal coliforms, molds, and yeasts. The study was developed through the collection of samples in a sterile container from three snack bars located in the municipality of Itapetinga-Bahia, whose criterion was that their production takes place in an artisanal way, being identified, and coded in A, B and C. The results showed that the mayonnaise served as a side dish in snack bars were contaminated in the two repetitions performed.  which can leave customers of these establishments susceptible to food outbreaks. This result points to a serious problem of non-compliance with good manufacturing practices. Therefore, it is suggested that new studies covering more establishments be carried out, that inspection actions be strengthened, that the handlers of these foods participate more frequently in training as part of the implementation of good manufacturing practices and that these establishments make the necessary adjustments to eliminate the risks of outbreaks due to microbiological contamination of sauces such as mayonnaise. DOI:https://doi.org/10.56238/interdiinovationscrese-089